A Narrative Inquiry Exploring Social Workers' Understanding of Yoga and Its Application in Professional Practice. Issue 2 (3rd April 2021) - Mensinga, Jo
ABSTRACT: Yoga is increasing in popularity. As a holistic practice, it is being applied and researched as a healing modality for physical ailments, assisting with mental health issues, and addressing traumatic symptoms. However, little is known about how social workers understand and include Yoga in their personal lives or professional practice. As part of a larger narrative study, practitioners in an Australian regional centre were asked: "What, if any, impact do embodied practices like Yoga have on your experience and your clients' experience?" This paper explores the stories told by three of the practitioners interviewed both individually and in focus groups. The dominant themes that emerged highlight that: a personal Yoga practice can be varied; the impact it has on professional outcomes is difficult to quantify; there is a lack of theoretical discussion about the body and embodied experience in social work; the challenges associated with introducing Yoga into social work practice are complex. IMPLICATIONS: Embodied practices such as Yoga provide social workers opportunities to increase self-awareness, their capacity to engage with clients and self-care. Theoretical understandings of the body and embodiment need to be better articulated in social work if embodied practices like Yoga are to be included in the professional conversation.